217 Histiocytes and the brain: a rare case of Rosai-Dorfman disease responsive to trametinib. Issue 6 (27th May 2022) - Hawken, Jonathan; Hu, Mo; Johnston, Ann; Edwards, Marc
Abstract : Rosai-Dorfman Disease (RDD) is a rare heterogenous systemic condition caused by histiocyte over-prolif- eration within various organ systems, which may manifest with neurological symptoms. We report the case of a 70-year-old female who presented with pan-hypopituitarism, and was found to have leptomeningeal enhancement and an infundibular mass lesion on MRI. Brain biopsy confirmed a histological diagnosis of RDD, and initially she was managed conservatively. Four years later her cognition, gait and level of functioning deteriorated. Serial MRIs showed slow progres- sion of the lesions. Treatment with pulsed methylprednisolone followed by an oral taper proved ineffec- tive. A multi-disciplinary team decision was made to start treatment with Trametinib (1mg once daily). A repeat MRI after 6 months showed a reduction in enhancing lesions with no new lesions. Her mobility and cognition also improved objectively. Treatment is ongoing and has been well tolerated with only a mild skin rash as a possible adverse reaction. Trametinib is an inhibitor of mitogen-activated extracellular signal regulated kinase enzymes (MEK1 and MEK2). It is typically used for melanoma, but there is emerging evidence of its effectiveness in RDD. Optimal treatment duration is not yet clearly established, and further research is needed to elucidate underlying disease mechanisms. drhawken@outlook.com